The Prince George Community Social Development Board: A case study of municipal inter-agency crime prevention. - Koch, Brigitte. (University of Ottawa (Canada), 1991)
This research examines the planning and organization of municipal inter-agency crime prevention through a case study of Prince George's Community Social Development Board. The focus of the Board is on social development: it attempts to tackle the social causes of crime. The methodology for the study includes an analysis of available documentation, including letters, memorandums and reports; interviews in Prince George with the ten members of the Community Social Development Board and the RCMP officer who initiated the Board and; observation of one Board meeting (May 1, 1991). Results of the interviews show that although the Board did have some benefits, it did not have clear objectives, it lacked leadership and it desperately needed a full-time executive director. In conclusion, municipal inter-agency crime prevention is a promising strategy to lower crime, and deserves to be given a second chance. (Abstract shortened by UMI.)
Keywords: Political Science, Public Administration.